2023
DOI: 10.1186/s12889-022-14945-5
|View full text |Cite
|
Sign up to set email alerts
|

Job burnout and its influencing factors in Chinese medical staffs under China’s prevention and control strategy for the COVID-19 pandemic

Abstract: Objective This study aimed to investigate the influencing factors of burnout among grassroots medical staff in China so as to provide a reference for improving their physical, psychological, and social statuses under China's prevention and control strategy for the COVID-19 pandemic and ensuring the sustainable supply of high-quality medical resources. Methods This study was performed on medical staff in five primary hospitals in Jiangsu Province, C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 35 publications
(30 reference statements)
1
8
0
Order By: Relevance
“…The percentage of rehabilitation therapy professionals working in private hospitals has experienced a signi cant rise, from 14% [25] before the pandemic outbreak to 21% after the outbreak. The emergence of this scenario primarily stems from a decline in earnings and a surge in employee turnover during the epidemic [26,27]. In comparison to private hospitals, public hospitals enjoyed a higher income per person prior to the outbreak [28], which resulted in a pronounced psychological discrepancy among public hospital staff, consequently leading to an elevated rate of resignations.…”
Section: Discussionmentioning
confidence: 99%
“…The percentage of rehabilitation therapy professionals working in private hospitals has experienced a signi cant rise, from 14% [25] before the pandemic outbreak to 21% after the outbreak. The emergence of this scenario primarily stems from a decline in earnings and a surge in employee turnover during the epidemic [26,27]. In comparison to private hospitals, public hospitals enjoyed a higher income per person prior to the outbreak [28], which resulted in a pronounced psychological discrepancy among public hospital staff, consequently leading to an elevated rate of resignations.…”
Section: Discussionmentioning
confidence: 99%
“…According to the Job Demand-Resources (JD-R) model, excessive work demands and lack of resources for medical staff due to COVID-19 events can gradually deplete staff energy and result in burnout [35]. When medical professionals are long-term exposed to such work environments characterized by high-risk, high-emotional demands, high workload and job requirements, lack of relaxation activities and uncertain security, they face an increased risk of job burnout [6,24]. Meanwhile, prolonged separation from family members and limited social support during the implementation of travel restrictions and quarantine requirements in response to the epidemic may lead to burnout among medical professionals [36,37].…”
Section: Relationship Between Covid-19 Event Strength and Job Burnoutmentioning
confidence: 99%
“…In response to COVID-19 variants with higher transmissibility, China adopted a new strategy called "Dynamic COVID-zero" from August 2021, and PHC providers play an important role in halting the spread of the epidemic in the community [23]. However, the surge in cases has resulted in medical staff working under high-pressure, high-load, and high-risk circumstances for extended periods, creating conditions conducive to burnout [24,25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Scholars such as Chen ( 14 ), Vranas ( 15 ), Magalh Magalhães ( 16 ), and Szczerbińska ( 17 ) respectively studied the burnout status and influencing factors of doctors and nurses in large general hospitals during the COVID-19 epidemic. Peng ( 18 ), Chen ( 19 ), and other scholars studied the current situation and influencing factors of job burnout of medical staff in primary medical institutions during the COVID-19 epidemic. Job burnout of medical staff during the pandemic has become a hot research topic at home and abroad, and it is found that most of the studies are concentrated in tertiary hospitals.…”
Section: Introductionmentioning
confidence: 99%